Predicting epiphyseal screw length in anterior plating of distal radial fractures - Letissier, Hoel; Dardenne, Guillaume; Stindel, Eric; Borotikar, Bhushan; Le Nen, Dominique; Kerfant, Nathalie (The Journal of hand surgery, European volume, 2020)
The purpose of this study was to determine whether optimal epiphyseal screw length could be predicted with reference to a given diaphyseal screw length when fixating a plate to the anterior surface of the distal radius. Computerized tomography scans of 40 wrists of 28 men and 12 women were semi-automatically segmented. A virtual anterior plate model was fixed to the distal radius. The mean maximal appropriate length of one diaphyseal screw and of the four distal epiphyseal screws were measured and linear regression analyses were performed. We found that the epiphyseal screw lengths were highly correlated to the diaphyseal screw length. Based on the data derived from measurements, we recommend epiphyseal screw lengths from ulnar to radial of 18, 18, 20 and 16 mm, respectively, if the diaphyseal screw is 14 mm or less. For diaphyseal screws longer than 14 mm we recommend epiphyseal screws of 20, 20, 22 and 18 mm. Using these recommended screw lengths as general guidelines may reduce the risk of intra-operative and postoperative extensor tendon injury.